Thermal, Deformation, and Degassing Remote Sensing Time Series (CE 2000–2017) at the 47 most Active Volcanoes in Latin America: Implications for Volcanic Systems. Issue 1 (12th January 2019) - Reath, K.; Pritchard, M.; Poland, M.; Delgado, F.; Carn, S.; Coppola, D.; Andrews, B.; Ebmeier, S. K.; Rumpf, E.; Henderson, S.; Baker, S.; Lundgren, P.; et al.
Abstract: Volcanoes are hazardous to local and global populations, but only a fraction are continuously monitored by ground‐based sensors. For example, in Latin America, more than 60% of Holocene volcanoes are unmonitored, meaning long‐term multiparameter data sets of volcanic activity are rare and sparse. We use satellite observations of degassing, thermal anomalies, and surface deformation spanning 17 years at 47 of the most active volcanoes in Latin America and compare these data sets to ground‐based observations archived by the Global Volcanism Program. This first comparison of multisatellite time series on a regional scale provides information regarding volcanic behavior during, noneruptive, pre‐eruptive, syneruptive, and posteruptive periods. For example, at Copahue volcano, deviations from background activity in all three types of satellite measurements were manifested months to years in advance of renewed eruptive activity in 2012. By quantifying the amount of degassing, thermal output, and deformation measured at each of these volcanoes, we test the classification of these volcanoes as open or closed volcanic systems. We find that 28% of the volcanoes do not fall into either classification, and the rest show elements of both, demonstrating a dynamic range of behavior that can change over time. Finally, we recommend how volcano monitoring could be improved through better coordination of available satellite‐based capabilities and new instruments. Key Points: Seventeen years of degassing, thermal, deformation, and Global Volcanism Program ground‐based data are analyzed for the 47 most active volcanoes in Latin America This study demonstrates the advantages of using a multiparameter approach for monitoring volcanoes while demonstrating the need for greater coordination The data are used to test the open and closed volcanic classification scheme, demonstrating the need for additional classifications